Reality of Distance Education in Arab Schools in Israel and its Obstacles as perceived by teachers - Jbareen, Ezdihar Omar (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of distance education in Arab schools inside Israel and its obstacles from the point of view of teachers, To achieve the objectives of the study, the researcher used the descriptive analytical method, by developing the study tool (the questionnaire). which included two main domains; The first is the reality of distance education, and the second axis is the obstacles to distance education. The study sample included (840) teachers working in Arab schools inside Israel. The results showed that the reality of distance education in general came to a medium degree, with a mean of (3.28 out of 5), and the skill domain came in the first rank with an mean (3.48), followed by the knowledge domain with mean (3.43) and then came in the third rank The evaluation field with an arithmetic average (3.24), followed in the last rank by the technical field with mean (2.96), and the results showed the presence of obstacles and difficulties, and they came from medium to large degree with mean of (3.29).
Keywords: Distance education; obstacles and difficulties